The Use of Flipbook Multimedia on Narrative Writing Ability and Creative Thinking Skills of Grade VI Elementary School Students - Rifa Nurhanifa; Atep Sujana; Wahyu Sopandi; Iswara P; Arrum A.H (International Conference on Elementary Education, 2023)
The ability to write narratives is one of the things that need to be developed for students at the elementary school level. The flipbook contains cartoon images of several story parts that students can develop themselves. This study aims to analyze the effect of flipbook multimedia on the ability to write narratives and creative thinking skills of grade VI elementary school students. This study uses a qualitative design with a descriptive analysis method. The research was conducted at one of the public elementary schools in Kasomalang District, Subang Regency. The participants of this study were 13 grade VI elementary school students. The data collection instruments were student activity observation sheets, teacher interviews, and activity documentation. Based on the results of the analysis carried out, it was found that multimedia flipbooks can facilitate students in learning to write narratives and improve students' creative thinking skills, this is evidenced by the results of student writing that are more varied than before, and students can work on narrative writing in less time than before.